Is diagnostic accuracy of Alvarado scoring feasible in acute surgery for management of acute appendicitis? - Malhotra, Mohinder Kumar; Sharma, Ram Gopal; Goyal, Subhash; Panwar, Udit; Singal, Kiran Kumar; Dwivedi, Sankalp (Bangladesh Journal of Medical Science, 2016)
Aim: To evaluate the usefulness and feasibility of the Alvarado scoring system in acute surgery in reducing the percentage of negative appendicectomy in our institute. Materials and Methods: A prospective study was conducted, comprising 100 patients, admitted to department of Surgery in Maharishi Markendeshwar Institute of Medical sciences & Research (M.M.I.M.S.R), Mullana, Ambala, India during the period October 2012 to July 2014 with a preliminary diagnosis of acute appendicitis. Patients of both sexes and all age groups were included in the study and their Alvarado scores calculated, on the basis of which patients were divided into three groups: group1 (alv. Score >7) , group 2 (alv. score 5-6), group 3 (alv. Score <4). The signs, symptoms, laboratory values, surgical interventions, and pathology reports of each patient were evaluated. Diagnosis was confirmed by histopathological examination. Sensitivity, specificity, and positive and negative predictive values of scoring system were calculated. Results: Out of 100 cases (82 males, 18 females), 76 Patients belonged to be in group1 (76%), 20 patients were in group 2 (20%) and 4 patients were in group 3 (4%). All 100 patients were operated, of which 86 patients found to have inflamed appendix (86%). 82 (82%) of operated patients were male and 18 (18%) were females. Out of 82 of operated males, 64 were having score > 7, 8 were having score 5-6 and 1 had score <4. Out of 18 operated females, 6 were having score > 7, 4 were having score 5-6, and 2 females had scoring <4. Negative appendectomy rate in our study was 14% which showed that Alvarado score helped in making diagnosis of acute appendicitis; thus reducing negative appendicectomy. Sensitivity and specificity of the Alvarado scoring system were found to be 83.7% and 71% respectively. Positive and negative predictive values were 94.7% and 83.3% respectively. Conclusion: Alvarado score can be used effectively in acute surgery in our setup to reduce the incidence of negative appendectomies in both male and females. It can be applied easily for acute surgery even by junior surgical colleagues with limited diagnostic facilities available to them. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.166-171